Ferroelastic phase transitions by 14N NMR spectra in [N(CH3)4]2CoCl4 and [N(CH3)4]2ZnCl4 single crystals. (September 2016) - Lim, Ae Ran
Abstract: Changes in the structural geometry of [N(CH3 )4 ]2 BCl4 (B=Co and Zn) crystals near the phase transition temperatures were studied by analyzing the 14 N nuclear magnetic resonance (NMR) spectra. Two physically inequivalent a-N(1)(CH3 )4 and b-N(2)(CH3 )4 groups were observed in these spectra. Abrupt changes in the resonance frequency and splitting of 14 N NMR signals near the phase transition temperatures were attributed to structural phase transitions, and the primary mechanism of these phase transitions exhibited ferroelastic characteristics. In addition, ferroelasticity of [N(CH3 )4 ]2 BCl4 was identified at low temperatures using optical polarizing microscopy. Graphical abstract: Highlights: Changes in the structural geometry. Two crystallographically different ions a-N(1)(CH3 )4 and b(2)-N(CH3 )4 . The existence of ferroelastic properties at low temperatures.